Self-Assembled Gels for Biomedical Applications - Truong, Warren Ty; Su, Yingying; Meijer, Joris T.; Thordarson, Pall; Braet, Filip (Chemistry, an Asian journal, 2011)
Natural and synthetic gel‐like materials have featured heavily in the development of biomaterials for wound healing and other tissue‐engineering purposes. More recently, molecular gels have been designed and tailored for the same purpose. When mixed with, or conjugated to therapeutic drugs or bioactive molecules, these materials hold great promise for treating/curing life‐threatening and degenerative diseases, such as cancer, osteoarthritis, and neural injuries. This focus review explores the latest advances in this field and concentrates on self‐assembled gels formed under aqueous conditions (i.e., self‐assembled hydrogels), and critically compares their performance within different biomedical applications, including three‐dimensional cell‐culture studies, drug delivery, and tissue engineering. Although stability and toxicity issues still need to be addressed in more detail, it is clear from the work reviewed here that self‐assembled gels have a bright future as novel biomaterials. Self‐assembled medicine! Emerging medical applications of self‐assembled gels (see picture) based on interactions between these materials with cells and tissues, such as drug delivery, 3D cell cultures, and tissue engineering, are discussed.